A escrita de Maura Lopes Cançado: um contraponto com a (des)articulação da linguagem do louco - Custódio, Márcia Moreira (2017)
This doctoral thesis aims to research and analyze the literary writing by Maura Lopes Cançado, with the assumption that exist relationship between literature and madness. The writer's works, Hospício é deus and O sofredor do ver, show aspects that particularize Maura's narrative and language the narrative that locate the writer in fracture with your time. Within the conception of "contemporary" of Giorgio Agamben, Maura inscribes her in the condition of disconnected, eccentric writer, in disagreement with her time. Privileging the theme of madness, the reading of her works promotes possible links between the life and the work of the author, hospice patient, setting the activity of Maura's literary creation, simultaneously, as place of memory, of denunciation, of resistance and experience’s bending. The postulates of thinkers such as Maurice Blanchot, Heloisa Buarque de Hollanda, Flora Sussekind, Michel Foucault, Erving Goffman and others support this reflection. Once the Maura's writing shows in its elaboration the structure and the theme of violence, repression and pain, giving voice to a community closed in hospice, the manifestation gives a testimonial content in his works, whose approach will by the studies Jaime Ginzburg and Márcio Seligmann-Silva.